THE ISLAMIC RELIGIOUS STUDIES TECHNICAL VOCABULARY (IRSTV): A CORPUS-BASED STUDY TO INFORM MATERIALS DEVELOPMENT - Srifani Simbuka, - (2019)
This study portrays the construction of a technical vocabulary list in the discipline of Islamic Religious Studies (IRS), which was called the Islamic Religious Studies Textbooks Vocabulary (IRSTV). The IRSTV was created based on the target corpus, the Corpus of Islamic religious studies textbooks an Indonesian State Institute for Islamic Studies (CIRST -ISIIS). The study also demonstrated ways of applying the corpus-based IRSTV list in informing vocabulary materials development for undergraduate EFL learners studying at Indonesian Islamic state-owned universities and colleges.A quantitative design was used as the method of this present study using the AntConc and AntWordProfile, both created by Laurence Anthony. To inform vocabulary materials development for IAIN/ISIIS EFL learners, the findings of this present study contributes in two ways:providing technical vocabulary and a tool for selecting texts for materials. Keywords: Corpus Linguistics, technical vocabulary, wordlist, corpus, ELT materials